2020
DOI: 10.3892/ol.2020.12264
|View full text |Cite
|
Sign up to set email alerts
|

Cell‑free DNA as a liquid biopsy for early detection of gastric cancer (Review)

Abstract: Gastric cancer (GC) is one of the most common malignant tumors with poor prognosis worldwide, mainly due to the lack of suitable modalities for population-based screening and early detection of this disease. Therefore, novel and less invasive tests with improved clinical utility are urgently required. The remarkable advances in genomics and proteomics, along with emerging new technologies for highly sensitive detection of genetic alterations, have shown the potential to map the genomic makeup of a tumor in liq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 114 publications
0
25
0
Order By: Relevance
“…In the last years, two studies [15,16] identified that cfDNA was able to distinguish GC patients from healthy individuals with an area under the curve (AUC) of 0.94 and 0.99, respectively. Nevertheless, the use of cfDNA for early GC detection is difficult to implement due to its low abundance in the early stage and the technical challenges in its detection [17]. Another approach was evaluated by Cohen et al, where the authors designed the CancerSEEK blood test.…”
Section: Circulating Free Dnamentioning
confidence: 99%
See 1 more Smart Citation
“…In the last years, two studies [15,16] identified that cfDNA was able to distinguish GC patients from healthy individuals with an area under the curve (AUC) of 0.94 and 0.99, respectively. Nevertheless, the use of cfDNA for early GC detection is difficult to implement due to its low abundance in the early stage and the technical challenges in its detection [17]. Another approach was evaluated by Cohen et al, where the authors designed the CancerSEEK blood test.…”
Section: Circulating Free Dnamentioning
confidence: 99%
“…However, the use of some of these biomarkers still has limitations. Thus, the use of cfDNA for early GC detection is difficult to implement due to the low abundance in early-stage GC and the technical challenges in its detection [17]. Furthermore, cfDNA is derived from cells that undergo necrosis or apoptosis, which might not reflect viable tumor cells [60].…”
Section: Proteinsmentioning
confidence: 99%
“…This assay allows selection of further cancer therapy [ 12 ]. Liquid biopsy is another method of diagnosis applied especially for leukemia and gastric cancer [ 13 , 14 ]. Advanced methods of cancer diagnosis include detection of circulating cancer cells (CRC) as well as next generation sequencing (NGS) that allows for genetic characterization of malignancies [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Circulating free DNAs (cfDNA) are free DNA fragments found in plasma, serum, or other body fluids. Physiological events, such as apoptosis or micrometastasis are the origin of cfDNAs in the body [1]. Previous studies showed that cfDNA level is 2-3-fold higher in cancer patients compared with healthy individuals [2].…”
Section: Introductionmentioning
confidence: 99%
“…The potential of cfDNA in cancer monitoring has emerged since the advent of liquid biopsy [3]. In cancer studies, cfDNAs are widely investigated for genomics and epigenomics patterns due to the fact that they are representative of the primary tumor, as well as their non-invasive nature; therefore, they could be feasible biomarkers in the clinic for cancer detection and more precise treatments [1]. Among several cfDNA studies, the 5-hydroxymethylcytosine (5hmC) is a specific DNA modification used in cancer monitoring, however, there is less attention in pan-cancer studies [4,5].…”
Section: Introductionmentioning
confidence: 99%